The Specialized Roles in Carotenogenesis and Apocarotenogenesis of the Phytoene Synthase Gene Family in Saffron - Ahrazem, Oussama; Diretto, Gianfranco; Argandoña Picazo, Javier; Fiore, Alessia; Rubio-Moraga, Ángela; Rial, Carlos; Varela, Rosa M.; Macías, Francisco A.; Castillo, Raquel; Romano, Elena; Gómez-Gómez, Lourdes (Frontiers in Plant Science, 2019)
Crocus sativus stigmas are the main source of crocins, which are glucosylated apocarotenoids derived from zeaxanthin cleavage that give saffron its red color. Phytoene synthase (PSY) mediates the first committed step in carotenoid biosynthesis in plants. Four PSY genes encoding functional enzymes were isolated from saffron. All the proteins were localized in plastids, but the expression patterns of each gene, CsPSY1a, CsPSY1b, CsPSY2, and CsPSY3, in different saffron tissues and during the development of the stigma showed different tissue specialization. The CsPSY2 transcript was primarily detected in the stigmas where it activates and stimulates the accumulation of crocins, while its expression was very low in other tissues. In contrast, CsPSY1a and CsPSY1b were mainly expressed in the leaves, but only CsPSY1b showed stress-light regulation. Interestingly, CsPSY1b showed differential expression of two alternative splice variants, which differ in the intron retention at their 5′ UTRs, resulting in a reduction in their expression levels. In addition, the CsPSY1a and CsPSY1b transcripts, together with the CsPSY3 transcript, were induced in roots under different stress conditions. The CsPSY3 expression was high in the root tip, and its expression was associated with mycorrhizal colonization and strigolactone production. CsPSY3 formed a separate branch to the stress-specific Poaceae homologs but was closely related to the dicot PSY3 enzymes.